Laboratory Anxiety: Prevalence and Overcoming the Challenges among Indian Secondary School Students - Chandni (SEAQIS Journal of Science Education, 2025)
The association of negative emotions with the triumph of scientific inquiry requires focus as an area of research, since it has long been established that learning by doing is the highest form of engagement in science. This study addresses laboratory anxiety, its prevalence, and the barriers that inhibit students' full participation. It also proposes a self-directed learning strategy to mitigate anxiety. An initial sample of 121 students, selected through purposive sampling, was studied to measure the prevalence in a study primarily conducted using a sequential explanatory mixed-methods approach. Then, 19 students who showed a high level of anxiety were interviewed to understand the cause behind anxiety, and they were further administered a self-directed learning strategy containing elements derived from the conclusions of student interviews. A significant prevalence of laboratory anxiety was found among school students. Based on the self-directed learning strategy, the results revealed a significant decrease in overall laboratory anxiety, and individual improvement was observed for components of the execution of experiment, laboratory safety, use of chemicals, and use of material and equipment. These findings highlight the need for curriculum interventions and revised teaching methodologies that support emotionally safe and effective science learning environments.